2012
DOI: 10.1177/1358863x12440117
|View full text |Cite
|
Sign up to set email alerts
|

Effect of sulfasalazine on inflammation and endothelial function in patients with established coronary artery disease

Abstract: Inflammation is critical for atherosclerosis development and may be a target for risk-reduction therapy. In experimental studies, activation of the inflammatory regulator, nuclear factor kappa B (NFlB), contributes to endothelial activation and reduced nitric oxide production. We treated patients with coronary artery disease with sulfasalazine, an inhibitor of NFκB, and placebo in a randomized, double-blind, crossover study design. Brachial artery flow-mediated dilation (FMD) and digital vascular function were… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
15
1

Year Published

2013
2013
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(17 citation statements)
references
References 37 publications
1
15
1
Order By: Relevance
“…Our results do not address the potential therapeutic efficacy of longer-term, lower-dose salsalate treatment in this or other groups. In contrast to short-term salsalate administration in the present study and previous investigation in overweight/obese adults [16], recent work in patients with type 2 diabetes [30] and coronary artery disease [37] found no improvements in FMD with longer-term administration of salicylate-based compounds (salsalate and sulfasalazine, respectively). These differences may result from differences in compounds and dosing, concurrent use of medications such as statins, ACE inhibitors and/or metformin that improve endothelial dysfunction, or different etiologies of endothelial dysfunction among these groups.…”
Section: Discussioncontrasting
confidence: 99%
“…Our results do not address the potential therapeutic efficacy of longer-term, lower-dose salsalate treatment in this or other groups. In contrast to short-term salsalate administration in the present study and previous investigation in overweight/obese adults [16], recent work in patients with type 2 diabetes [30] and coronary artery disease [37] found no improvements in FMD with longer-term administration of salicylate-based compounds (salsalate and sulfasalazine, respectively). These differences may result from differences in compounds and dosing, concurrent use of medications such as statins, ACE inhibitors and/or metformin that improve endothelial dysfunction, or different etiologies of endothelial dysfunction among these groups.…”
Section: Discussioncontrasting
confidence: 99%
“…The relative contribution of inflammation versus hypercholesterolemia in atherogenesis is a recurrent question in the field of atherosclerosis . Short‐term intervention with sulfasalazine, an inhibitor of NFκB, in patients with coronary artery disease has not been successful in reversing endothelial dysfunction, whereas in a small group of patients with recent acute coronary syndrome, inhibition of the leukotriene‐generating enzyme 5‐lipoxygenase reduced inflammation and plaque progression . More studies are ongoing to further decipher the exact contribution of inflammation in atherogenesis …”
Section: Discussionmentioning
confidence: 99%
“…Salsalate therapy has had conflicting results on endothelial function in patients with HIV . Tabit and colleagues found no effect of sulfasalazine therapy on endothelial function in patients with coronary artery disease . Similarly, Goldfine et al found no difference in FMD in diabetic subjects treated with high‐dose salsalate therapy .…”
Section: Discussionmentioning
confidence: 99%